Revelation and Divination in Ndembu Ritual: Symbol, Myth, and Ritual - Turner, Victor W. (Cornell University Press, 2018)
The core of this book is a complete description of two important Ndembu rituals of affliction (Chihamba and Kayong'u) , and an analysis of the system of ideas underlying more than a dozen modes of divination. Written by an internationally-known social scientist, the book demonstrates how the study of small-scale events may reveal as much about what it means to be a human being in society as do grand macrosocial and macrocultural surveys.Drawing on two and a half years of fieldwork, Victor Turner offers two thorough ethnographic studies of Ndembu revelatory ritual and divinatory techniques, with running commentaries on symbolism by a variety of Ndembu informants. Striking a personal note in the introductory chapter, Turner acknowledges his indebtedness to Ndembu ritualists for alerting him to the theoretical relevance of symbolic action in understanding human societies. He believes that ritual symbols, like botanists' stains, enable us to detect and trace the movement of social processes and relationships that often lie below the level of direct observation.
paid
Keywords: African Hist & Diaspora; Religious Studies